Analisis Kandungan Karbon pada Vegetasi Mangrove di Desa Lembar Kabupaten Lombok Barat - Siti Wardatul Jannah; Firman Ali Rahman; Alfian Pujian Hadi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
The mangrove ecosystem is one of the vegetation that has a role as carbon mitigation in coastal areas, especially in port activity areas that can produce large amounts of carbon, such as in Lembar Harbor, Lembar Village, West Lombok Regency. The purpose of this study was to analyze the carbon content in the root and leaf tissue contained in each type of mangrove in the Lembar Harbor Area, Lembar Village, West Lombok Regency. This type of research is descriptive quantitative, with purposive random sampling method, which starts with taking root and leaf samples on each different mangrove species, and testing is carried out based on the Walkley & Black method to obtain tissue carbon content. Based on the results of the study, found 8 (eight) families consisting of 11 species, including: Avicennia lanata, Avicennia marina, Lumnitzera racemosa, Bruguiera gymnorrhiza, Rhizophora stylosa, Ceriops decandra, Scyphiphora hydrophyllaceae, Excoecaria agallocha, Thespesia populnea, Xylocensis, and Ipome pescaprae. The condition of the environmental parameters of the mangrove ecosystem in Lembar Village is still in good condition, in accordance with the quality standards of water health quality, Decree of the State Minister of the Environment Number 51 of 2004 concerning sea water quality standards for biota. The average organic carbon content of root tissue was 43.47 ± 3.10 %C and leaves was 43.87 ± 3.66 %C. The highest organic carbon content in root tissue was found in Xylocarpus moluccensis (47.46 %C), and the lowest was in Ipomea pescaprae (41.49 %C), while the highest organic carbon content in leaf tissue was in Bruguiera gymnorrhiza (50.60 %C), and the lowest was Avicennia lanata (38.99 %C). Based on Tukey's further test that the value of organic content stored in the root and leaf tissue of mangroves was not significantly different (> 0.05) with a statistical test value of 0.76.